Geochemical consequences in shallow aquifers from the long‐term presence of CO2 in a natural field: The case of Florina Basin, W. Macedonia, Greece. Issue 4 (21st December 2015) - Gemeni, Vasiliki; Vasilatos, Charalampos; Koukouzas, Nikolaos; Kanellopoulos, Christos
Abstract: Natural CO2 fields can be used to identify trapping mechanisms, the fate and the geochemical consequences of geologically stored CO2 in shallow aquifers. The Florina Basin in Greece is regarded as a CO2 naturally leaking analog due to millions of years of gas accumulation in a Tertiary sand formation. This research was conducted in order to identify the CO2 fingerprints and to investigate and evaluate the factors controlling the groundwater quality in the basin. Leaking CO2 is observed in the aquifers and at the surface. The basin is filled with clastic sediments. It can provide information regarding the fate of CO2 and the possible impacts that can be used as reference in demonstration and industrial projects. Water sampling campaigns were conducted to determine the impact of the gas‐water long‐term interactions in the shallow aquifers. The CO2 has increased the concentration (in relation to other water samples from the basin) of certain elements like Fe, Mn, Na, Cl, and Br but only in few cases exceeds the EU drinking limit. The chemistry of the groundwater in the Florina Basin aquifers was found to be controlled mainly by the CO2 ‐water‐rock interactions due to the mineralogy of the aquifers (calcite and silicates including pyroxenes and chlorite). Metal attenuation processes have prevented the aquifers from brine contamination. Considering the Florina Basin is a natural analog for studying the leaking and migration pathways of stored CO2 and that only minor affects have been identified in the groundwater chemistry, the conclusions of this research are promising for the possible usage of a basin of similar geology and lithology for deep CO2 storage. © 2015 Society of Chemical Industry and John Wiley & Sons, Ltd